2019
DOI: 10.1038/s41598-019-44055-z
|View full text |Cite
|
Sign up to set email alerts
|

Static and dynamical isomerization of Cu38 cluster

Abstract: The lowest-energy geometrical and electronic structures of Cu 38 cluster are investigated by density-functional calculations combined with a genetic algorithm based on a many body semi-empirical interatomic potential, the traditional FCC-truncated Octahedron (OH) and an incomplete-Mackay icosahedron (IMI) are recognized as the two lowest energy structures (energetically degenerate isomers) but with different electronic structures: a semiconductor-type with the energy-gap of 0.356 eV for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…as the low-energy structure. The Highest Occupied Molecular Orbital (HOMO)-Lowest Unoccupied Molecular Orbital (LUMO) gap of the IMI structure is 0.24 eV (0.356 eV reported in previous DFT studies(Zhang et al, 2019). In contrast, the HOMO-LUMO gap for the IIMI structure is 0.30 eV.…”
mentioning
confidence: 77%
“…as the low-energy structure. The Highest Occupied Molecular Orbital (HOMO)-Lowest Unoccupied Molecular Orbital (LUMO) gap of the IMI structure is 0.24 eV (0.356 eV reported in previous DFT studies(Zhang et al, 2019). In contrast, the HOMO-LUMO gap for the IIMI structure is 0.30 eV.…”
mentioning
confidence: 77%
“…In addition to that gold is a good conductor of heat and electricity, and is unaffected by air and most reagents. Noble-metal (Cu, Ag, and Au) clusters have attracted much attention in scientific and technological fields because of their thermodynamic, electronic, optical and catalytic properties in nano-materials [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, many researchers have observed that, beyond Au −1 25 , the lowsymmetry core-shell structures dominate the low-energy clusters, and the hollowcage structures are unlikely to exist in larger size due to the strong relativistic effects [14]. Chuanchuan Zhang et al, [5], worked on the lowest-energy geometrical and electronic structures of Cu −1 38 clusters which are investigated by density functional calculations combined with a genetic algorithm based on a many body semi-empirical interatomic potential, the traditional FCC-truncated Octahedron (OH) and an incomplete-Mackay icosahedron (IMI) are recognized as the two lowest energy structures (energetically degenerate isomers) but with different electronic structures: a semiconductor-type with the energy-gap of 0.356 eV for the IMI and a metallic-type with negligible gap for the OH, which is in good agreement with the experimental results. The electron affinity and ionization potential of Cu −1 38 are also discussed and compared with the observations of the ultraviolet photoelectron spectroscopy experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that gold is a good conductor of heat and electricity, and is unaffected by air and most reagents. Noble-metal (Cu, Ag, and Au) clusters have attracted much attention in scientific and technological fields because of their thermodynamic, electronic, optical and catalytic properties in nano-materials [6,7].…”
Section: Introductionmentioning
confidence: 99%